Early dexamethasone treatment for septic shock patients: a prospective randomized clinical trial - Cicarelli, Domingos Dias; Vieira, Joaquim Edson; Benseñor, Fábio Ely Martins (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Sepsis and septic shock are very common conditions among critically ill patients that lead to multiple organ dysfunction syndrome (MODS) and death. Our purpose was to investigate the effi cacy of early administration of dexamethasone for patients with septic shock, with the aim of halting the progression towards MODS and death. DESIGN AND SETTING: Prospective, randomized, double-blind, single-center study, developed in a surgical intensive care unit at Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: The study involved 29 patients with septic shock. All eligible patients were prospectively randomized to receive either a dose of 0.2 mg/kg of dexamethasone (group D) or placebo (group P), given three times at intervals of 36 hours. The patients were monitored over a seven-day period by means of the sequential organ failure assessment score. RESULTS: Patients treated with dexamethasone did not require vasopressor therapy for as much time over the seven-day period as did the placebo group (p = 0.043). Seven-day mortality was 67% in group P (10 out of 15) and 21% in group D (3 out of 14) (relative risk = 0.31, 95% confi - dence interval 0.11 to 0.88). Dexamethasone enhanced the effects of vasopressor drugs. CONCLUSIONS: Early treatment with dexamethasone reduced the seven-day mortality among septic shock patients and showed a trend towards reduction of 28-day mortality.